Study of Ethnobotany in Ginger (Zingiber officinale Rosc.) in Tamiang Village, Banten - Gut Windarsih; Asih Perwita Dewi; Deni Mulyana; Arif Gozali Warso Saputro; Muhammad Efendi (Al-Hayat: Journal of Biology and Applied Biology, 2023)
Ginger (Zingiber officinale Rosc.) is one of plant species widely used as traditional medicine.The aim of the study was to determine the utilization and ethnobotany of ginger for local communities in Tamiang village, Serang district, Banten. The type of research was descriptive. The research method was the exploratory survei and the participatory rural appraisal. The data collection techniques were conducted through interview, questionnaire, field observation, and documentation. The respondents were determined using purposive sampling and snowball sampling methods. Based on the results of research, the three local varieties of ginger used by local communities in Tamiang village, namely emprit, elephant, and red gingers. The utilization of ginger by local communities in that village was for food and drink ingredients, spices, medicinal ingredients, and ornamental plant. A total of 34.21% of respondents had consumed red ginger to increase the immune system to prevent the Covid-19 virus infection during the pandemic period.